PERFORMANCE ASSESSMENT OF VARIABLE-DEPTH CULTIVATION TECHNIQUES IN REDUCING AGRICULTURAL ENERGY CONSUMPTION - Tadjimuratova Aziza; Ruzimov Sanjarbek (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Tillage is the backbone of crop production, but it is also a massive drain on farm finances due to high fuel consumption. Traditional “blanket” tillage—where a plow is set to one depth for an entire field—ignores the natural diversity of soil. This article explores Variable Depth Tillage (VDT), a precision farming method that adjusts plowing depth in real-time. By synthesizing data from multiple international studies, we demonstrate that VDT can reduce fuel use by 30%, lower energy demands by 50%, and protect soil from long-term erosion [1][2][7].